THE EMERGENCE OF NATIONAL POP ART IN UZBEKISTAN - Khojageldiyeva Mahfuza Ergash qizi; Chorshanbeyiv Suyunbek Nasriddin o’g’li (Journals Park Publishing, 2022)
This article provides information about the period of introduction of pop art in Uzbekistan and the representatives of Uzbek art who contributed to the development of this art. The process of formation and development of Uzbek pop art Since the second half of the XIX century, such terms as "variety", "variety concert", "variety art" began to come into use among the people.
Keywords: Variety art